On the taxonomic status of Asthenodipsas vertebralis (Boulenger, 1900) (Squamata: Pareidae) in Borneo with the description of a new species - Quah, Evan S. H.; Lim, Kelvin K.p.; Grismer, L. Lee (Zootaxa, 2021)
The taxonomic status of Asthenodipsas vertebralis in Borneo has been plagued with uncertainty over the last eighty years. An examination of museum collections resulted in the discovery of a voucher specimen of A. vertebralis from Sarawak, East Malaysia that confirms the presence of the species in Borneo and a previously unrecognised species, Asthenodipsas ingeri sp. nov. from Mount Kinabalu, Sabah. Asthenodipsas ingeri sp. nov. can be differentiated from its congeners by the combination of an absence of preoculars and suboculars, 1st and 3rd pair of infralabials in contact, two pairs of posterior inframaxillaries, supralabials 3–5 (sometimes 3 & 4) in contact with orbit, 15/15/15 rows of dorsal scales, presence of sharp vertebral keel, and divided subcaudals. This study highlights the importance of careful re-examination of museum collections that could potentially harbour new species hiding in plain sight. These discoveries also add to the growing number of reptile and amphibian species being described from Borneo that shows no signs of abating but are already potentially threatened by the continued deforestation and developments on the island.